Bioactive cellulose acetate nanofiber loaded with annatto support skeletal muscle cell attachment and proliferation - Santos, Ana Elisa Antunes dos; Cotta, Tiago; Santos, João Paulo Ferreira; Camargos, Juliana Sofia Fonseca; Carmo, Ana Carolina Correia do; Alcântara, Erika Gabriele Alves; Fleck, Claudia; Copola, Aline Gonçalves Lio; Nogueira, Júlia Meireles; Silva, Gerluza Aparecida Borges; Andrade, Luciana de Oliveira; Ferreira, Roberta Viana; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Electrospinning emerged as a promising technique to produce scaffolds for cultivated meat in function of its simplicity, versatility, cost-effectiveness, and scalability. Cellulose acetate (CA) is a biocompatible and low-cost material that support cell adhesion and proliferation. Here we investigated CA nanofibers, associated or not with a bioactive annatto extract (CA@A), a food-dye, as potential scaffolds for cultivated meat and muscle tissue engineering. The obtained CA nanofibers were evaluated concerning its physicochemical, morphological, mechanical and biological traits. UV-vis spectroscopy and contact angle measurements confirmed the annatto extract incorporation into the CA nanofibers and the surface wettability of both scaffolds, respectively. SEM images revealed that the scaffolds are porous, containing fibers with no specific alignment. Compared with the pure CA nanofibers, CA@A nanofibers showed increased fiber diameter (420±212 nm vs. 284±130 nm). Mechanical properties revealed that the annatto extract induces a reduction of the stiffness of the scaffold. Molecular analyses revealed that while CA scaffold favored C2C12 myoblast differentiation, the annatto-loaded CA scaffold favored a proliferative state of these cells. These results suggest that the combination of cellulose acetate fibers loaded with annatto extract may be an interesting economical alternative for support long-term muscle cells culture with potential application as scaffold for cultivated meat and muscle tissue engineering.